2021
DOI: 10.1159/000513521
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Normative Data on Singing Voice Parameters of Children and Adolescents with Average Singing Activity Using the Voice Range Profile

Abstract: <b><i>Purpose:</i></b> The purpose of this study was to establish and characterize age- and gender-specific normative data of the singing voice using the voice range profile for clinical diagnostics. Furthermore, associations between the singing voice and the socioeconomic status were examined. <b><i>Methods:</i></b> Singing voice profiles of 1,578 mostly untrained children aged between 7.0 and 16.11 years were analyzed. Participants had to reproduce sung tones a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
0
0
1
Order By: Relevance
“…The maximum frequency was 397 Hz for males and 725 Hz for females. But in the current study, the minimum frequency was found to be 87 Hz and the maximum was 554 Hz [6]. There seems to be a considerable difference between the 16 yr old teens and the 18 year old adults, which can again be attributed to the continuation of the anatomical and physiological variations, which probably extends beyond the pubertal age as studied by various authors.…”
Section: Methodscontrasting
confidence: 47%
“…The maximum frequency was 397 Hz for males and 725 Hz for females. But in the current study, the minimum frequency was found to be 87 Hz and the maximum was 554 Hz [6]. There seems to be a considerable difference between the 16 yr old teens and the 18 year old adults, which can again be attributed to the continuation of the anatomical and physiological variations, which probably extends beyond the pubertal age as studied by various authors.…”
Section: Methodscontrasting
confidence: 47%